Deteksi dan Identifikasi Spesies Meloidogyne Penyebab Umbi Berbintil pada Kentang Asal Sulawesi Utara - Utami, Budi Sri; Supramana, Supramana; Giyanto, Giyanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Root-knot nematode (Meloidogyne spp.). is one of the main constraint of potato production in North Sulawesi. Little is known about Meloidogyne species infecting potatoes in North Sulawesi. Therefore, research was conducted to identify Meloidogyne spp. on potatoes in North Sulawesi and further study their relationship with related species from other countries. Infected potato tubers with pimple-like knot symptom were collected from three potato production centers, i.e. Kakenturan (South Minahasa), Purworejo (East Bolaang Mongondow) and Singsingon (…?? Bolaang Mongondow). Morphological identification was conducted based on the perineal pattern of the female; whereas molecular identification was conducted by PCR using specific primer for ITS-rDNA, followed by DNA sequencing and phylogenetic analysis. Two Meloidogyne species were identified i.e. M. javanica (samples form Kakenturan, Purworejo and Singsingon) and M. incognita (samples from Purworejo). M. javanica and M. incognita from North Sulawesi are similar to the related species from China with homology level of 97.5 % and 100 %, respectively.